1989
DOI: 10.1210/jcem-69-1-186
|View full text |Cite
|
Sign up to set email alerts
|

Temporary Ovarian Failure in Thyroid Cancer Patients after Thyroid Remnant Ablation with Radioactive Iodine

Abstract: We studied ovarian function retrospectively in 66 women who had regular menstrual cycles before undergoing complete thyroidectomy for differentiated thyroid cancer and subsequent thyroid remnant ablation with 131I. Eighteen women developed temporary amenorrhea accompanied by increased serum gonadotropin concentrations during the first year after 131I therapy. No correlation was found between the radioactive iodine dose absorbed, thyroid uptake before treatment, oral contraceptive use, or thyroid autoimmunity. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
62
0
7

Year Published

2006
2006
2015
2015

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 88 publications
(72 citation statements)
references
References 3 publications
3
62
0
7
Order By: Relevance
“…In contrast, not all investigators have confirmed the benefit of adjuvant therapy with 131 I in this group (2), with this therapy resulting in 2 relevant problems, the need for iatrogenic hypothyroidism (11) and radioiodine toxicity (1,(3)(4)(5)(6)(7)(8)(9)(10). With respect to the latter, a low activity (1.1-1.85 GBq ) is applied to minimize the adverse effects of radioiodine.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In contrast, not all investigators have confirmed the benefit of adjuvant therapy with 131 I in this group (2), with this therapy resulting in 2 relevant problems, the need for iatrogenic hypothyroidism (11) and radioiodine toxicity (1,(3)(4)(5)(6)(7)(8)(9)(10). With respect to the latter, a low activity (1.1-1.85 GBq ) is applied to minimize the adverse effects of radioiodine.…”
Section: Discussionmentioning
confidence: 99%
“…Using MIRD (38), the estimated radiation in testes and ovaries would be 85 mGy and 140 mGy, respectively, when 3,700 MBq (100 mCi) of 131 I are administered during euthyroidism (as for the preparation with rhTSH). Specific studies on thyroidectomized patients during hypothyroidism suggest that the same activity would result in a testicular radiation of 86 mGy (39) to 120 mGy (40); the radiation in the ovaries would be much higher than estimated by MIRD (9), and an average radiation of 740 mGy would be obtained for the salivary glands (41). Interstudy comparison is inappropriate because of differences in the characteristics of the patients, in the preparation protocol, in the assessment techniques, and between examiners.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Ovarian function is only temporarily compromised by radioiodine (2)(3)(4)(5), with permanent infertility being rare (2). Thus, many women with thyroid cancer treated with radioiodine may become pregnant, and it is therefore important to evaluate the evolution of these pregnancies and the consequences for the offspring.…”
mentioning
confidence: 99%
“…Amenorrhea due to temporary ovarian dysfunction (18,19) and depression of spermatogenesis (20) after radioiodine treatment have been observed.…”
Section: Discussionmentioning
confidence: 99%